Obrazy války v italských městech v kázáních observanta a v cestovním deníku řeholníka z první poloviny 15. století - Jan Stejskal (Theatrum Historiae)
At the beginning of the Renaissance, nobody asked questions about the natural state of mankind – that is, whether it is war or peace – as they had verifiably done on the threshold of the High Middle Ages. Dante defined war as an undesirable phenomenon devastating “poor Italy”. The fresco depicting an allegory of good and bad government, which decorates the Siena town hall, unambiguously associates war and the related devastation with bad government. The concord of the town inhabitants and the resulting peace were preached by Bernardino of Siena († 1444) in his Lent sermons. Not even Ambrogio Traversari († 1439), who set out on extensive and tireless journeys throughout (not only) Italy in the early 1430s and left a unique account of them in his travel diary entitled Hodoeporicon, had doubts about this appraisal. The diary captures his journeys in 1431–1435 and gives a unique picture of the towns he visited and the war conflicts he witnessed. It also mentions a thankless role of a friar who found himself (and sometimes physically) in the midst of the war between two enemies.